Valsalva retinopathy induced by handstand: a case report - Toshiya Miyaki; Teruyo Kida; Shou Oosuka; Masanori Fukumoto; Takaki Sato; Masayuki Nakajima; Tsunehiko Ikeda (BMC Ophthalmology, 2020)
Abstract Background Valsalva retinopathy is known to occur as a sudden preretinal or sub-internal limiting membrane hemorrhage induced by a rapid rise in venous pressure following increased intrathoracic or intraabdominal pressure. Here we report a case of Valsalva retinopathy that was probably induced by straining that occurred due to following a handstand. Case presentation A 15-year-old boy became aware of decreased visual acuity in his left eye immediately after doing a handstand for approximately 10 s during physical education class, and subsequently visited a local clinic on the same day. Upon examination, a vitreous hemorrhage (VH) in the posterior pole of the fundus was found in his left eye, and he was subsequently referred to our department 7 days later. Upon examination, the VH around the optic nerve head of the left eye appeared to be resolved, and an oval-shaped sub-internal limiting membrane (sub-ILM) hemorrhage was found in the superonasal side of the optic nerve head. No abnormalities were observed in the macular area. Four months later, the sub-ILM hemorrhage was found to have spontaneously resolved. Subsequent fluorescein angiography examinations revealed no abnormal findings at the lesion site. Conclusions In this patient, we hypothesize that the Valsalva retinopathy was induced by straining that occurred due to a handstand, and that the resultant sub-ILM hemorrhage progressed to VH.